2023
DOI: 10.1111/jssr.12836
|View full text |Cite
|
Sign up to set email alerts
|

Christ, Country, and Conspiracies? Christian Nationalism, Biblical Literalism, and Belief in Conspiracy Theories

Abstract: When misinformation is rampant, "fake news" is rising, and conspiracy theories are widespread, social scientists have a vested interest in understanding who is most susceptible to these false narratives and why. Recent research suggests Christians are especially susceptible to belief in conspiracy theories in the United States, but scholars have yet to ascertain the role of religiopolitical identities and epistomological approaches, specifically Christian nationalism and biblical literalism, in generalized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Most studies use singleitem measures of self-reported religiosity (e.g., Galliford and Furnham, 2017), of the importance of religion or God in one's life (e.g., Mancosu et al, 2017), or of the frequency of church attendance (e.g., Lobato and Zimmerman, 2019). Studies using more extensive multiple-item measures of religiosity tend to report stronger associations (Jasinskaja-Lahti and Jetten, 2019;Łowicki et al, 2022;Yendell and Herbert, 2022;Frenken et al, 2023;Walker and Vegter, 2023). Only one study distinguishes different religious attitudes, finding positive effects of religious fundamentalism but not of centrality of religious beliefs on conspiracism (Łowicki et al, 2022).…”
Section: Religion Spirituality and Conspiracy Beliefsmentioning
confidence: 99%
“…Most studies use singleitem measures of self-reported religiosity (e.g., Galliford and Furnham, 2017), of the importance of religion or God in one's life (e.g., Mancosu et al, 2017), or of the frequency of church attendance (e.g., Lobato and Zimmerman, 2019). Studies using more extensive multiple-item measures of religiosity tend to report stronger associations (Jasinskaja-Lahti and Jetten, 2019;Łowicki et al, 2022;Yendell and Herbert, 2022;Frenken et al, 2023;Walker and Vegter, 2023). Only one study distinguishes different religious attitudes, finding positive effects of religious fundamentalism but not of centrality of religious beliefs on conspiracism (Łowicki et al, 2022).…”
Section: Religion Spirituality and Conspiracy Beliefsmentioning
confidence: 99%